Carbon dioxide capture through reaction with potassium hydroxide and reject brine: A kinetics study - Aya A-H. Mourad (17380423) (2022)
The aim of this research is to investigate the reaction kinetics for a modified Solvay process based on KOH. The global reaction rate was measured within 3−15% CO2 inlet concentration, 10−50 °C reaction temperature, 30–190 g/L KOH concentration, 400–2000 mL/min CO2 gas flow rate, and 1–5 bar total applied pressure range, changing one factor at a time while keeping the values of the remaining parameters fixed. As part of each set of experimental runs, temporal changes in ion reduction and pH value were also monitored. The results revealed that the reaction rate is directly proportional to the increase in the inlet CO2 concentration. This finding was supported by CO2 uptake, whereby the maximum value of almost 0.69 g CO2/g KOH was achieved at the highest CO2 inlet concentration of 15%. However, the selected range of reaction temperature and KOH concentration exerted no influence on the overall CO2 absorption rate, which remained nearly constant within the selected ranges for these parameters. Under the chosen operating conditions, a first-order overall reaction rate with respect to CO2 concentration was established, whereby the reaction rate constant (k) was∼ 0.0003 mol/(L·min). Other Information Published in: International Journal of Greenhouse Gas Control License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijggc.2022.103768